J.K. Lasser's small business taxes 2026 : your complete guide to a better bottom line - Weltman, Barbara, 1950- (John Wiley & Sons, Inc., 2026)
Small business owners in the US face enough challenges without overpaying tax. Despite this, millions of small businesses miss out on crucial deductions, tax credits, and tax-saving moves every year, resulting in higher-than-necessary tax bills. In J.K. Lasser's Small Business Taxes 2023: Your Complete Guide to a Better Bottom Line, renowned attorney and small business advocate Barbara Weltman offers a thorough and exhaustively researched roadmap to legally minimizing your tax liability and maximizing your deductions and credits.